Silica deposition on zirconia via room-temperature atomic layer deposition (RT-ALD): Effect on bond strength to veneering ceramic - Bitencourt, Sandro Basso [UNESP]; Hatton, Benjamin D.; Bastos-Bitencourt, Natália Almeida; dos Santos, Daniela Micheline [UNESP]; Pesqueira, Aldiéris Alves [UNESP]; De Souza, Grace Mendonca (Elsevier, 2022)
Purpose: To develop and to characterize a hybrid interface between yttria-stabilized zirconia (Y-TZP) transformed layer and silica-based nanofilm to enable a better bonding between Y-TZP and a veneering ceramic. Material and methods: Sixty-six fully-sintered rectangular Y-TZP specimens were distributed into 6 groups, according to the surface treatment applied: C (control): no treatment; Al: 27 μm-alumina particle abrasion; Ht: hydrothermal treatment in autoclave for 15h; Si20: 20 cycles of silica deposition using room-temperature atomic layer deposition (RT-ALD); Si40: 40 cycles of RT-ALD; Ht + Si40: hydrothermal treatment followed by 40 cycles of RT-ALD. RT-ALD was performed by the sequential exposure of specimens to vapor of tetramethoxysilane orthosilicate (TMOS) and ammonium hydroxide (NH4OH). Y-TZP surface wettability and shear bond strength (SBS) between Y-TZP and the veneering ceramic were analyzed for all groups after surface treatments. One-way ANOVA and Tukey's HSD test were used for data analysis (p ≤ 0.05). Results: The highest contact angle was observed for the control group (64.46 ± 6.09 θ), while the lowest values (p < 0.001) were presented after Si20 (29.85 ± 4.23 θ) and Si40 (30.37 ± 5.51 θ) treatments. Hydrothermal treatment (49.3 ± 2.69 θ) and alumina abrasion (45.84 ± 4.12 θ) resulted in intermediate contact angle values. The highest SBS values were observed for Al (16.74 ± 1.68 MPa) and Ht (15.27 ± 2.11 MPa) groups (p < 0.018). Groups Si20 (9.66 ± 1.22 MPa), Si40 (9.33 ± 2.11 MPa), Ht + Si40 (9.37 ± 1.02 MPa) and C (12.54 ± 2.64 MPa) all resulted in similar SBS results (p > 0.998). Conclusion: The experimental treatments proposed enhanced surface wettability, but shear bond strength between Y-TZP and veneering ceramic was not improved. Alumina particle-abrasion improved SBS values while a decrease in wettability was observed.
Keywords: Hydrothermal treatment; Shear bond strength; Surface hydrophilicity; Surface treatment